Antimicrobial and physiochemical properties of films and coatings prepared from bio-fiber gum and whey protein isolate conjugates. (June 2023) - Jin, Tony Z.; Yadav, Madhav P.; Qi, Phoebe X.
Abstract: Bio-fiber gum (BFG) was conjugated with whey protein isolate (WPI) at the mass ratio of 3:1 WPI:BFG through a Maillard-type reaction. A composite of BFG and chitosan (CHI) was also prepared at the same mass ratio (3:1 CHI:BFG) to yield CHI + BFG. WPI:BFG and CHI + BFG containing 1% carvacrol were used to develop antimicrobial food packaging films and coatings. In vitro and in vivo tests were applied to assess the antimicrobial efficacies of the films against E. coli, Listeria, Salmonella, spoilage fungi, and background bacteria. The physicochemical properties of the films were examined to evaluate their potential for food packaging applications. Both films drastically reduced the populations of Listeria, E. coli, and native microorganisms on tomatoes and fresh-cut apples, stored at 4 °C for up to 7 and 21 days, respectively. They also significantly inhibited Salmonella and bread fungi growth in media. Furthermore, WPI:BFG conjugate films sustained their antifungal properties for more prolonged and repeated uses than the CHI + BFG composite films. We also demonstrated that WPI:BFG conjugate films evidenced lowered water solubility, decreased carbon dioxide and oxygen permeability, and superior mechanical strength than the CHI + BFG composite films. These films and coatings can be utilized as viable barriers for various foods by headspace releasing and direct food surface coating. Highlights: WPI and BFG, mass ratio 3:1 (WPI:BFG), were conjugated through a Maillard reaction. WPI:BFG proved strong antimicrobial properties as food packaging films and coatings. WPI:BFG films had lowered water solubility, oxygen and carbon dioxide permeability. Headspace release, direct contact, bread fungi tests showed WPI:BFG's superiority.